Metagenome-assembled microbial genomes (n = 3,448) of the oral microbiomes of Tibetan and Duroc pigs - Hong Hu; Ying Huang; Fuyan Yang; Liangru Ma; Junjie Zhang; Xu Deng; Nan Ma; Kunping Wang; Ye Tao; Qin Lin; Yanfei Li; Xi Bai; et al. (Scientific Data)
Abstract Compared with leaner breeds, local Chinese pig breeds have distinct intestinal microbial, as determined by metagenomic techniques, and the interactions between oral microorganisms and their hosts are also gradually being clarified. However, the high host genome content means that few metagenome-based oral microbiomes have been reported. Here, we combined dilution-based metagenomic sequencing and binning approaches to extract the microbial genomes from the oral microbiomes of Tibetan and Duroc pigs. The host contamination rates were reduced to 13.64%, a quarter of the normal metagenomic level (65.25% on average). Medium–high-quality metagenome-assembled genomes (MAGs; n = 3,448) spanning nine phyla were retrieved and 70.79% were novel species. Of the nonredundant MAGs, only 13.37% were shared, revealing the strong disparities between Tibetan and Duroc pigs. The oral microbial diversity of the Duroc pig was greater than that of the Tibetan pig. We present the first large-scale dilute-based metagenomic data on the pig oral microbiome, which should facilitate further investigation of the functions of oral microorganisms in pigs.